Freshwater Resource Exploitation: New Security Challenge for Africa - Anyu, J. Ndumbe; DZEKASHU, William G. (Advances in Social Sciences Research Journal, 2020)
Population growth and human activities such as freshwater resource exploitations continue to have shattering effects on ecological dynamics. These effects are likely not unrelated to issues emanating from climate change and global warming. There is adequate scientific evidence that supports shifting trends in the ecosystem and specifically relating to increased water use and loss of wetlands; that poses a new security challenge for Africa especially, and which without proper intervention, could be catastrophic; resulting in food shortage and profound implications on biodiversity conservation. Many measures have been put in place intended to arrest excessive water extraction; the measures include co-management, encouragement of local community adaptation methods, and good governance. It is unclear whether these methods can catch up with the speed of depletion of the water resources. There is fear that future scarcity in water resources could compound with other issues plaguing Africa to result in conflicts.